AN ASSESSMENT OF THE NUTRITIONAL STATUS OF UNDER-FIVE CHILDREN OF TEA GARDEN WORKERS OF SONITPUR DISTRICT, ASSAM, INDIA - Dr. Alok Kumar Das; Dr. Rupali Baruah; Dr. Shashanka Shekhar Chakraborty; Dr. Chandi Ram Kalita (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Malnutrition is the major cause of morbidity and mortality among under-five children especially in the developing countries. Though the tea tribe peoples gives significant contribution in Indian economy but still they are the most neglected communities in our society due to which malnutrition is highly prevalent in their children. Materials and Methods: A community based cross-sectional study conducted among 400 under-five children of Tea Garden workers of Sonitpur District, Assam, the children were selected by using multistage random sampling. A pre-planned, pre-tested, semi-structured interview schedule was used to gather data. Anthropometric measurements were recorded. Data analysis were performed using IBM SPSS (v30.0.0), applying the Chi-square test for association, with statistical significance at p<0.05. Results: Among 400 participants 52.5% were females and 47.5% were males, among which maximum of children belongs to 0-15 months of age group. 38.8% of children were born underweight, 47% were partially immunized, and 9.3% of mothers did not exclusively breastfeed. Significant characteristics related with underweight were birth weight (p<0.001), immunization status (p=0.003), exclusive breastfeeding (p=0.008), and complementary feeding (p=0.021). Stunting was associated with birth weight, mother’s age, initiation of breastfeeding, and immunization status (p < 0.05). Religion (p=0.022), preterm birth, place of delivery, exclusive breastfeeding, initiation of breastfeeding, complementary feeding, and MUAC all had a significant relationship with wasting. Conclusion: Malnutrition is still a significant public health problem among under- five children of tea garden workers with low immunization status, exclusive breastfeeding and low birth weight. Our study findings recommend for the awareness building among the tea garden workers in regard to boost maternal child nutrition initiative, encourage IEC on child care and feeding. Educate mothers on managing diarrhoea and appropriate feeding techniques.